THE EFFECT OF JOB TRAINING ON THE PERFORMANCE OF SECURITY SQUAT 1 ALPA AT PT. GLOBAL ARROW, MANDAU DISTRICT, BENGKALIS REGENCY - Muhammad Erwin; Zuriaty (EL-EMIR Institute, 2025)
This study aims to determine the effect of job training on the performance of Security Squat 1 Alpha at PT. Global Arrow, Mandau District, Bengkalis Regency. The method used is quantitative with data collection techniques through questionnaires to security members. Data analysis was carried out by testing validity, reliability, normality, heteroscedasticity, simple linear regression, determination test (R²), and t-test. The results of the validity and reliability tests indicate that all research instruments are valid and reliable. Normality and heteroscedasticity tests prove that the data is normally distributed and free from symptoms of heteroscedasticity. The results of simple linear regression show that job training has a positive effect on security performance. The coefficient of determination (R²) value of 0.996 indicates that job training contributes 99.6% to improving performance, while the rest is influenced by other factors. The t-test produces a significant value (Sig. <0.05), so it can be concluded that job training has a significant effect on the performance of Security Squat 1 Alpha at PT. Global Arrow. Thus, job training is an important factor in increasing employee effectiveness and productivity.